2011
DOI: 10.3892/etm.2011.419
|View full text |Cite
|
Sign up to set email alerts
|

Sequential analysis of diethylnitrosamine-induced hepatocarcinogenesis in rats

Abstract: Abstract. In the present study, we examined the sequential changes of diethylnitrosamine (DEN)-induced hepatocarcinogenesis in Wistar rats. After 14 weeks of DEN treatment, hyperplastic nodules developed as a consequence of the appearance of renewed hepatocytes, degenerated hepatocytes, oval cells and fibrotic changes. Total bilirubin and alanine aminotransferase levels were significantly higher in the DEN group compared to the control group throughout the experimental period. Our data may prove beneficial to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…The increased liver/body mass ratio is considered as a primary criterion to determine HCC development [31]. During pilot experiments, it was observed that two doses of 1 mg/kg b.w.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The increased liver/body mass ratio is considered as a primary criterion to determine HCC development [31]. During pilot experiments, it was observed that two doses of 1 mg/kg b.w.…”
Section: Resultsmentioning
confidence: 99%
“…Histopathology is widely used to diagnose liver carcinoma in the patients and has also been employed to ascertain progression of DEN, a genotoxic agent, induced HCC in the animal models [31]. AFB1 is a common genotoxic agent which is considered accountable for prevalence of HCC in the human population; however, information is limited on histopathology of HCC induced by this agent, except an earlier report suggesting formation of liver foci as neoplastic lesions during AFB1 carcinogenesis in rat model [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations